The Birth of Modern Economics and “Crossfertilization” of Sciences - Davidko, Natalya (Verbum, 2013)
The term ‘crossfertilization of metaphors’ from discipline to discipline was used by Dr. Rolf Von Eckartsberg (1983) to describe mutually enriching metaphorical projections between autonomous disciplines aimed at helping scientists to form a particular view of reality or develop their own theories. However, this interesting path of studying conceptual mappings has not received sufficient consideration on the part of researchers though there are insightful observations and case studies of the phenomenon in question in the works of many authors. The current article is an attempt to study the mechanisms underlying the formation of a new conceptual domain – economics – through an interaction of knowledge structures between the new and established intellectual disciplines. Metaphor, analogy, and comparison are “mediators” in this interaction and vehicles in the conceptualization of economic reality and in expressing new cognitive content.